Hybrids based on coumarins and their anticancer activities: A bibliometric analysis - Wilson Cardona-Galeano, Howard Ramirez-Malule, David Gómez-Ríos (Journal of Applied Pharmaceutical Science, 2023)
Coumarins are a family of benzopyrones widely spread in the natural kingdom. These compounds have been related to beneficial effects on human health, e.g., reducing the risk of cancer, among other diseases. In this contribution, a bibliometric analysis based on the results of the Scopus database was performed. The Scopus database was selected for data collection, and VOSviewer 1.6.18 was used for data analysis and visualization. A total of 458 documents related to coumarins were indexed in Scopus in the timespan of 1993–2022. Articles and reviews related to coumarins showed a clear increase in the number of published papers per year between 2008 and 2022. The main areas of knowledge of those records were: (i) pharmacology, toxicology, and pharmaceutics, (ii) chemistry, and (iii) biochemistry, genetics, and molecular biology. Here, the studies have been focused on the synthesis of hybrid molecules based in coumarins, experimental studies of cytotoxicity and antiproliferative activity in cancer cell lines in vitro and in vivo, molecular docking as a tool for unveiling the molecular mechanisms of action and experimental absorption, distribution, metabolism, and excretion studies. The most productive countries in studies related to coumarin derivatives are currently India, China, and Egypt. Those countries also showed the most robust collaboration network.
Keywords: Coumarins, coumarin hybrids, anticancer activity, bibliometric analysis